The dragon at the North Pole - Klimo, Kate.; Shroades, John (New York : Random House, 2013)
Using magic snowshoes, cousins Jesse and Daisy travel to the North Pole to retrieve their pet dragon.
Keywords: Santa Claus -- (Fictitious character) -- Fiction; Dragons -- Fiction; Magic -- Fiction; Christmas -- Fiction; Cousins -- Fiction